Pelatihan Penguatan Pendidikan Karakter Remaja Upaya Pencegahan Penggunaan Narkoba Di Karang Taruna Karet Setia Budi - Maududi, Mukhlish Muhammad; Rahman, Nurlina; Said, Ahmad (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2025)
Character education can be interpreted as ethics education, moral education, value education, character education, which aims to develop students' abilities in determining good and bad, maintaining what is good, and applying these good in everyday life. The purpose of implementing this Community Service is to increase Partners' knowledge about Character Education so that it can become a stronghold in the person of each participant to dare to refuse invitations to use Narcotics. The implementation method in this counseling activity uses face-to-face and still pays attention to health protocols with the capacity of counseling participants around 15 participants of the Management and Members of Karang Taruna Kelurahan Karet, Setia Budi District, South Jakarta. From the results of the Community Service Program activities, results were obtained based on the Post-test , there was an increase in knowledge of the dangers of narcotics and sanctions for users and dealers and an increase in knowledge of character education.